IMPLEMENTASI MENGENALKAN HURUF AL-QUR’AN DENGAN MEDIA BERMAIN FLASHCARD DI TAAM DARUL HUDA - Dede Nurul Qomariah; Jenal Abidin; Nendah Nurjannah (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2023)
The ability of children to recognize the letters of the Qur'an in Taam Darul Huda is still low. Almost all students know hijaiyyah letters, but have not been able to pronounce and write letters without seeing examples. The purpose of this study is to find out how the implementation of introducing the letters of the Qur'an with the media playing flashcards in Ta'am Nurul Huda. This type of research is a case study with a qualitative approach. Data collection techniques were carried out through observation, in-depth interviews and documentation studies. The results of the study show that the implementation of introducing the letters of the Qur'an with the media playing flashcards carried out by teachers at Taam Nurul Huda can actually help students memorize hijaiyah letters. The learning approach designed by the teachers is carried out through four stages, namely the preparation, implementation, self-learning, and evaluation stages.